Physical Chemical Characterization, Determination of Antioxidant Activity and Phytochemical Screening of Gambir Claw Herbal Tea (Uncaria gambir) - Lucky Hartanti; Asri Mulya Ashari; Rita Kurnia Apindiaty; Gusti eva Tavita; Rafdinal Rafdinal; Desriani Lestari; Warsidah Warsidah (Jurnal Biologi Tropis, 2022)
Uncaria gambir is a member of Rubiaceae family. Information related to antioxidants and the use of this plant in the food and cosmetic industry has been widely reported. This study aims to determine the physicochemical properties, phytochemical content and antioxidant activity of herbal tea made from gambir claw, which was collected from the Pontianak City area of ​​West Kalimantan. Determination of physicochemical properties is based on measuring the parameters of pH, water content, ash content and organoleptic including taste, odor and color when dissolved in water. Phytochemical screening was carried out using specific reagents to determine the presence of flavonoid compounds, tannins, alkaloids and saponins. Antioxidant activity was determined using the free radical scavenging method 2,2-diphenyl-1-picrylhydrazyl (DPPH). From the results of the measurement of the physical and chemical properties of gambir claw herbal tea, the pH, ash content, moisture content and powder conditions met the requirements of SNI No 3836 of 2013, phytochemical screening showed positive results for flavonoid and tannin compounds, and antioxidant activity was obtained at 88,398 ppm, classified as a strong antioxidant.